2006
DOI: 10.1373/clinchem.2005.059691
|View full text |Cite
|
Sign up to set email alerts
|

Time Profile of Appearance and Disappearance of Circulating Placenta-Derived mRNA in Maternal Plasma

Abstract: The ranges of the RQ values were calculated by use of the equation: RQ ϭ 2 Ϫ⌬⌬Ct , with ⌬⌬Ct ϩ SD and ⌬⌬Ct Ϫ SDs. The Micro Fluidic Cards detect a 2-fold difference in gene expression at the 99.7% confidence level. The efficiencies of all target and reference amplifications were nearly identical as analyzed by serial dilutions using 2, 1, 0.5, 0.25, and 0.125 ng of calibrator cDNA. When we plotted the log input amount of cDNA vs the ⌬Ct values, the slope was Ͻ0.1. The correlation coefficients were always Ͼ0.95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 9 publications
2
29
0
1
Order By: Relevance
“…Previous maternal plasma transcriptomic profiling studies have shown that certain trophoblast-specific transcripts and the overall fractional placental contribution increase with gestation (20,39,40). The fraction of fetal-derived RNA increases from only 3.7% in early pregnancy to 11.28% in late pregnancy (19,20).…”
Section: Noninvasive Elucidation Of Placental Cellular Dynamics Durinmentioning
confidence: 97%
“…Previous maternal plasma transcriptomic profiling studies have shown that certain trophoblast-specific transcripts and the overall fractional placental contribution increase with gestation (20,39,40). The fraction of fetal-derived RNA increases from only 3.7% in early pregnancy to 11.28% in late pregnancy (19,20).…”
Section: Noninvasive Elucidation Of Placental Cellular Dynamics Durinmentioning
confidence: 97%
“…Since fetal-derived mRNA is rapidly cleared from maternal circulation following delivery (10,11), antepartum and postpartum samples were compared with paired newborn umbilical cord blood samples to identify unique fetal biomarkers in maternal whole blood. Our hypothesis was that if specific gene transcripts were detected in pregnant women prior to delivery as well as in their infants' cord blood, yet were significantly reduced or absent in maternal blood within 24 to 36 hours of delivery, these gene transcripts could theoretically originate from the fetus (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Placental RNA was detected as early as the 4th week of gestation and rapidly cleared postpartum [13] , and placenta-specific RNA transcripts coding for hPL, ␤ -hCG and CRH have been detected in maternal blood of normal pregnant women and in those affected by trophoblast diseases [14] . Finally, Lo et al [32] analyzed the allelic ratio of a single nucleotide polymorphism of the placenta-derived placenta-specific 4 (PLAC4) mRNA in maternal plasma and Concu et al [33] demonstrated that mRNA provides a gender-independent marker to distinguish between normal and pathological pregnancies by measuring rapid clearance of mRNA for PLAC1 gene in maternal blood after delivery .…”
Section: Discussionmentioning
confidence: 99%
“…Besides recent findings in the study of circulating DNA, there is growing interest in the diagnostic potential of circulating RNA. Placental RNA can be detected as early as the 4th week of gestation and is rapidly cleared postpartum [13] . As already shown for DNA, the placenta has been suggested to be the main source of circulating RNA.…”
Section: Introductionmentioning
confidence: 99%